The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1097/rct.0b013e318230d905
|View full text |Cite
|
Sign up to set email alerts
|

Liver Metastases From Colorectal Cancer Treated With Conventional and Antiangiogenetic Chemotherapy

Abstract: Both CT-p and MR-DWI can detect therapy-induced modifications in lesion vascularization before significant changes in size are evident.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(18 citation statements)
references
References 28 publications
0
18
0
Order By: Relevance
“…Metastatic lesions to the liver have shown a significant increase in ADC values following systemic chemotherapy that precedes changes in lesion size 129,130 . Interestingly, a recent study by Marugami et al showed significant overlap in ADC values between responding and non-responding colorectal metastatic lesions following intra-arterial chemotherapy.…”
Section: Liver Applicationsmentioning
confidence: 99%
“…Metastatic lesions to the liver have shown a significant increase in ADC values following systemic chemotherapy that precedes changes in lesion size 129,130 . Interestingly, a recent study by Marugami et al showed significant overlap in ADC values between responding and non-responding colorectal metastatic lesions following intra-arterial chemotherapy.…”
Section: Liver Applicationsmentioning
confidence: 99%
“…Using radiofrequency ablation, decreased ADC was observed in the periphery of the ablation zone and correlated with local tumour progression [ 35 ] . Two studies found that for liver metastases of colorectal cancer, non-responding lesions had significantly lower pre-treatment mean ADCs than responding lesions [ 36 , 37 ] , but this was not confirmed in a third study [ 38 ] .…”
Section: Clinical Applications Of Dw-mri For Monitoring Treatment Resmentioning
confidence: 99%
“…A reduction in BF and BV was observed less than 48 hours after commencing antiangiogenic treatment in carcinoid liver metastases [ 21 ] . CP has been suggested as predictor of response in colorectal liver metastases [ 22 ] . The applicability of CTp has increased since the introduction of wider CT detectors and periodic spiral techniques allowing for 15–16-cm craniocaudal coverage with sufficiently short image frequency.…”
Section: Liver Metastasesmentioning
confidence: 99%